Implementasi Metode Cost Plus Pricing dan Algoritma Forward Chaining Berbasis Web - Sapto Wibowo; Ratih Titi Komala Sari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Nowadays the economy is an important factor in the survival of the society as well as the state. One of the competence needed as a strategy for economic problems in terms of buying and selling goods offered, particularly the selling price of the product. As a support for the Society 5.0 era, this research is conducted to ease the setting of the selling price with economic methods and algorithms. The technique used to set the selling price is Cost Plus Pricing. In the application of the method, this system will generate the product selling price collaborated with the Forward Chaining algorithm to provide recommendations on the profit margin determined based on several facts that have been processed from a set of kaggle data. These recommendations can support or compare the value of the margin that a user wants. The test is carried out with the Stress Testing system using the Apache Jmeter tools resulting in an error value of 1%, std.deviation and a good increase in throught so that the server performance of the selling price determination application can still survive well.